2018
DOI: 10.18320/jimd/201805.0272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of undergraduate dental students in typodont preparation for all-ceramic crowns

Abstract: Background: All-ceramic crown (ACC) preparations are widely used in day-to-day dental clinical practice. Objectives: This study aimed to evaluate all-ceramic crown preparations performed by pre-clinical dental students at the College of Dentistry, Jazan University in Saudi Arabia and to compare the quality of the preparations between male and female groups. Materials and Methods: A total of 95 ivory teeth were prepared by fourth-year dental students (44 males, 51 females). The students prepared a maxillary rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Mobaraki et al reported a significant difference between the male and female sex concerning MD reduction [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mobaraki et al reported a significant difference between the male and female sex concerning MD reduction [ 8 ].…”
Section: Discussionmentioning
confidence: 99%